How do doctoral students in STEM fields engage in scientific knowledge practices? - Jenna Vekkaila; Viivi Virtanen; Jani Kukkola; Liezel Frick; Kirsi Pyhältö (EARLI, 2019)
Knowledge creation is at the core of scientific endeavour. As early career researchers, doctoral students take part in knowledge creation through engaging in various knowledge practices and make their original contribution to knowledge, and become   experts in their particular domain. However, our understanding of what doctoral knowledge practices entails is still insufficient. For this study, a total of 34 doctoral students from STEM fields, including natural sciences, bio- and environmental sciences and medicine were interviewed to gain a better understanding of the kinds of knowledge practices in which doctoral students in the sciences engage. The data were collected with semi-structured interviews, which were qualitatively content analysed. The results showed that the participants mostly described activities that were established everyday knowledge practices of the researcher community (75 %), whereas practices that were innovative (25 %), entailing transformation of the current practices and developing new ones, were less often reported. Moreover, the practices were typically collective, involving the students, their supervisors or other members of their research groups (67 %). Further investigation showed that the participants were typically actively engaged in knowledge practices (79 %) rather than just adapting existing ones (13 %). Perceiving oneself as a bystander was even less typical (8 %). The significance of this study lies in exploring doctoral students' self-reported knowledge practices in STEM fields, and demonstrates that they perceive themselves as actively and collaboratively engaged in creating knowledge.